2020
DOI: 10.21203/rs.3.rs-56902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting therapy-resistant lung cancer stem cells via disruption of the AKT/TSPYL5/PTEN positive-feedback loop

Abstract: Cancer stem cells (CSCs) are regarded as essential targets to overcome tumor progression and therapeutic resistance; however, practical targeting approaches are limited. Here, we identify testis-specific Y-like protein 5 (TSPYL5) as a CSC-associated factor that promotes stemness and epithelial-to-mesenchymal transition in therapy-resistant non-small cell lung cancer (NSCLC) cells. Aberrantly activated PI3K/AKT pathway in therapy-resistant NSCLC cells promotes TSPYL5 phosphorylation at threonine-120 (pT120), wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
0
1
Order By: Relevance
“…Previous studies have shown that A549 cells are more than 80% ALDH1 + (23). In contrast, we found that H460 cells have very low expression of ALDH1 + (25).…”
Section: Birc5 Highly Expressed In Malignant Lung Cancercontrasting
confidence: 84%
“…Previous studies have shown that A549 cells are more than 80% ALDH1 + (23). In contrast, we found that H460 cells have very low expression of ALDH1 + (25).…”
Section: Birc5 Highly Expressed In Malignant Lung Cancercontrasting
confidence: 84%